The COMPARISON OF VASCULAR CALCIFICATION AND MINERAL BONE DISEASE IN NON-DIALYSIS (CKD4/5ND) VS DIALYSIS DEPENDENT (CKD5D) PATIENTS - Salahuddin; Malik Nadeem Azam; Khalid Mehmood Raja; Abdul Wahab Mir; Taleah Tahir; Faryal Riaz Khan; Abdul Rehman Arshad; Batool Butt; Wahaj; Ahsan (Journal of Ayub Medical College Abbottabad, 2022)
Background: Chronic kidney disease (CKD) has been a highly prevalent medical condition in all parts of the world affecting the haemostasis of the body in number of ways. Epidemiological data suggest that no region of the world has been spared from this condition and both developing and developed countries equally share the burden of this disease. Objective was to compare the vascular calcification and mineral bone disease in non-dialysis vs dialysis patients suffering from chronic kidney disease at a tertiary care hospital of Pakistan. It is a Comparative study, conducted at the Department of nephrology Pak Emirates Military Hospital Rawalpindi. Four months from November 2020 to February 2021. Methods: A total of 310 cases were included in the study, which were diagnosed as chronic kidney disease in nephrology department by a consultant nephrologist on basis of National Kidney Foundation/Kidney Disease Outcome Quality Initiative (NKF/KDOQI) 2002. They were divided into two equal groups by block randomization. Group I had the patients who were not dependent on dialysis (CKD4/5ND) while group II had dialysis dependent patients. Abdominal aorta, mitral and tricuspid valves were assessed to look for vascular calcification. Calcium, phosphate and parathyroid hormone levels were done to assess the mineral bone profile. Results: Out of 310 patients, 192 (61.9%) patients were males and 118 (38.1%) were females. 98 (31.6%) had evidence of vascular calcification while 212 (68.4%) did not have vascular calcification. 147 (47.4%) had hypocalcaemia, 167 (53.8%) had hyperphosphatemia while 98 (31.6%) patients had raised Parathyroid hormone levels. Regression analysis revealed that vascular calcification and abnormal mineral bone profile was significantly present more among patients who were dependent on dialysis (p-value<0.05). Conclusion: Bone mineral disease and vascular calcification were consistent findings among patients suffering from chronic kidney disease. Patients who were dependent on dialysis were more prone to develop these complications as compared to those who were not dependent on dialysis.